Student Economic Empowerment Through Business Capital Scholarships - Zami Salsabela; Uliyatul Mu’awwanah; Muhammad Asyaddu Hubballillah (SAFE-Network, 2026)
This study aims to examine the implementation of the Business Capital Scholarship Program as a form of productive Islamic philanthropy in the economic empowerment of students at Al-Falah Assunniyah University Kencong. This study uses a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, involving the Vice Rector III as the main informant and students receiving the Business Capital Scholarship Program. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing, with data validity tested using source triangulation and methodological triangulation. The research findings indicate that the Business Capital Scholarship Program is not only used as financial assistance, but also plays a role in empowering students' economics by strengthening their existing productive businesses. Assistance is provided flexibly according to students' business needs, both in the form of cash and productive assets. This program contributes to increasing business capacity and sustainability, and helps meet students' educational needs during their studies. In addition, the distribution of assistance is influenced by social capital in the form of social networks and trust within the campus environment. A trust-based approach allows students to manage business capital assistance with a greater emphasis on business development rather than strict administrative oversight. The findings of this study indicate that the integration of productive Islamic philanthropy, social capital, and a trust-based approach can be an alternative model for student economic empowerment in higher education institutions.